Anatomical and Functional Differences in the Sex-Shared Neurons of the Nematode C. elegans - Kim, Dongyoung; Kim, Byunghyuk (Frontiers in Neuroanatomy, 2022)
Studies on sexual dimorphism in the structure and function of the nervous system have been pivotal to understanding sex differences in behavior. Such studies, especially on invertebrates, have shown the importance of neurons specific to one sex (sex-specific neurons) in shaping sexually dimorphic neural circuits. Nevertheless, recent studies using the nematode C. elegans have revealed that the common neurons that exist in both sexes (sex-shared neurons) also play significant roles in generating sex differences in the structure and function of neural circuits. Here, we review the anatomical and functional differences in the sex-shared neurons of C. elegans. These sexually dimorphic characteristics include morphological differences in neurite projection or branching patterns with substantial changes in synaptic connectivity, differences in synaptic connections without obvious structural changes, and functional modulation in neural circuits with no or minimal synaptic connectivity changes. We also cover underlying molecular mechanisms whereby these sex-shared neurons contribute to the establishment of sexually dimorphic circuits during development and function differently between the sexes.